POLA NAMA MASYARAKAT KETURUNAN TIONGHOA - Suharyo, Suharyo (HUMANIKA, 2013)
ABSTRACT Ethnic Chinese community in Indonesia since 1966 has been "forced" to change their name to the Indonesian name by Presidential Decree number 127/U/Kep/12/1966. The reason why they change their name to the Indonesian one concerned with racial issues, but also they long lived in Indonesia actually they did not mastering the Chinese language. To find that out, here performed literature review by taking the data source in the mass media; especially advertising grief, books/ journals research, and interviews are limited. Keywords: Pattern of name, ethnic Chinese community, Indonesian name.